Dérives impactant la pérennisation de la philosophie pour enfants (P4C) - Emmanuèle Auriac-Slusarczyk; Juliette Robert; Julie Pironom; Hélène Maire (Éducation et Socialisation)
The present paper examines the presuppositions that might accompany the current diversified practices of Philosophy for Children (P4C). A double system of tensions is presented on a theoretical level, based on recent literature on the benefits of P4C. The theoretical hypothesis of a renewal of expectations adjusted to certain characteristics of our societies is put forward, notably the short-circuiting of reflexive reason by the nudge trend and the self-development movement; each individual could distort the horizon of P4C, which would no longer correspond to Lipman’s promises. A survey explores 330 responses that define this practice and identify the difficulties and skills associated with P4C. The average age for starting P4C is 6 years (+ or - 2/3 years). Conversely, the responses indicate tensions between sometimes existential, sometimes cultural objectives which, in line with our theoretical position, hinder the idea of a consensual P4C program.